FACTORS ASSOCIATED WITH BREASTFEEDING ADHERENCE IN INFANTS WITH OROFACIAL CLEFTS: A SCOPING REVIEW - Batista, Nayara Tomazi; Antonio, Camila Trettene; Bom, Gesiane Cristina; Farinha, Francely Tineli; Von Kostrisch, Lilia Maria; Mazzo, Alessandra; Trettene, Armando dos Santos (Cogitare Enfermagem, 2024)
Objective: To map the factors associated with breastfeeding adherence in infants with orofacial clefts. Method: Scoping review according to the recommendations of the Joanna Briggs Institute, with a search carried out in March 2023 in the PubMed, CINAHL, Web of Science, SCOPUS, EMBASE, LILACS, ProQuest and BDTD databases. Results: A total of 31 documents were selected. Factors associated with adherence to breastfeeding included: anatomical complexity of the cleft, pre- and post-natal guidance/training, desire to breastfeed, previous experience, knowledge of the benefits of breastfeeding, use of palatal obturators, use of feeding tube, social, family, and professional support, milking and offering by utensils and early performance of cheiloplasty. Conclusion: Although the complexity of the cleft is a factor that cannot be changed early on, the other variables that influence adherence to breastfeeding can be intervened upon. Thus, the support of all those involved in the breastfeeding process is fundamental for its optimization.